High-resolution, low-dose phase contrast X-ray tomography for 3D diagnosis of human breast cancers - Zhao, Yunzhe (National Academy of Sciences, 2012)
Mammography is the primary imaging tool for screening and diagnosis of human breast cancers, but ∼10–20% of palpable tumors are not detectable on mammograms and only about 40% of biopsied lesions are malignant. Here we report a high-resolution, low-dose phase contrast X-ray tomographic method for 3D diagnosis of human breast cancers. By combining phase contrast X-ray imaging with an image reconstruction method known as equally sloped tomography, we imaged a human breast in three dimensions and identified a malignant cancer with a pixel size of 92 μm and a radiation dose less than that of dual-view mammography. According to a blind evaluation by five independent radiologists, our method can reduce the radiation dose and acquisition time by ∼74% relative to conventional phase contrast X-ray tomography, while maintaining high image resolution and image contrast. These results demonstrate that high-resolution 3D diagnostic imaging of human breast cancers can, in principle, be performed at clinical compatible doses.